PENGARUH MOTIFASI KERJA, IKLIM KERJA, DAN KINERJA GURU TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA SMA NEGERI SE KABUPATEN PADANG PARIAMAN - Sri Ulfa Sentosa, Zuharnita, Bustari Muchtar, (Menara Ilmu, 2019)
This research aimed to find out and to analyze: (1) The influence of teachers’ working motivations and teachers’ working atmospheres toward Economic Senior High School teachers’ performances in Padang Pariaman. Regency, (2) The influence of teachers’ working motivation, teachers’ working atmospheres and Economic teachers’ performances toward Senior High School students’ learning results of Economic subject in Padang Pariaman Regency. This research was causal-descriptive research. The population was 65 Economic Teachers. The sampling technique was proposionate random sampling and the total sample was 32 Economic teachers. Primary data were attained from questionnaire and secondary data were taken from students’ Economic slearning result at the end of semester. The data were analyzed through path analysis using SPSS program version 18.0. The result showed that (1) Working motivation and working atmosphere had significant influence toward Economic teachers’ performances in Padang Pariaman Regency. It was proved that Fcount = 19.02 > Ftable= 3,30 with significant value 0.000 < α 0.05. It meant that when teachers had better motivations in teaching and more condusive working atmospheres, their performances would be higher. (2) Working motivations, working atmospheres, and Economic teachers’ performances had significant influence toward Senior High School students’ learning results of Economic subject in Padang Pariaman Regency. It was proved that Fcount = 19.1 > Ftable = 3,30 with significant value 0.0000 < α 0.05. It meant that when teachers had better working motivations, working atmospheres, and performances, students learning result of Economic subject would be higher. Key words: Working Motivation, Working Atmospheres, Teacher’s Perfomance, Learning Result